Visualization of deep convective image sequences - DaPonte, John S.; Parikh, Jo Ann (Visual Information Processing VIII, 1999)
The primary objective of this project is to define a methodology to depict the motion of deep convective cloud systems as observed form satellite imagery. These clouds are defined as clusters of pixels with Cloud Top Pressure (IPC) <EQ 440 millibars and Cloud Optical Thickness (TAU) >= 23 which are high in the atmosphere and sufficiently thick to produce significant rainfall. Clouds are one of the major factors in understanding the earth's climate. Evaluating cloud motion is important in understanding atmospheric dynamics and visualizations are vital because they provide a good way to observe change. IPC and TAU values have been collected for April of 1989 from the International Satellite Cloud Climatology Project, low resolution database for the northern latitudes between 30 and 60 degrees. Each of the 240 IPC and 240 TAU images consisted of 12 rows and 144 columns with each pixel representing a 280 km square on the globe collected in three-hour intervals. Individual images were color coded according to land, sea and clouds before being put into motion. Six animations have been produced which start with the original images, progress to include daily composite images and culminate with a collage. Animations of the original images have the advantage of relatively short intervals between still frames but have many undefined pixels, which are eliminated in the composites. The results of this project can serve as an example of how to improve the visualization of time varying image sequences.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00232 tex.type: [object Object]
Keywords: Animation; Atmospheric turbulence; Cloud motion dynamics; Cloud optical thickness; Cloud top pressure; Clouds; Database systems; Deep convective cloud systems; Image segmentation; Imaging systems; International satellite cloud climatology; Motion compensation; Satellite imagery; Time varying image sequences; Visualization; Weather satellites; dept.csc